THE IMPACT OF MATERNAL ANAEMIA ON BIRTH OUTCOMES, INCLUDING BIRTH WEIGHT, GESTATIONAL AGE, AND NEONATAL HEALTH (International Journal of Food and Nutritional Sciences, 2022)
This research mainly helps to better understand how maternal anemia affects delivery improvements, this study centers around three key areas which consist of the birth weight of the baby, the gestational period chronological age, and the well-being of the newborn. A process of the use of a combination of methodologies, it examines data that is quantitative to identify relationships and generates qualitative knowledge which helps to identify underlying mechanisms. The results highlight strong associations connecting maternal anemia and decreased pregnancy weight, elevated probability of preterm delivery, as well as weakened newborn health markers. These findings highlight how important it is for focused initiatives to raise maternal nutrition levels, further develop prenatal care, as well as ultimately raise birth quality as well as neonatal general well-being.A mixed-methods research strategy is used in this study, incorporating both qualitative and quantitative methods. The everyday experiences and viewpoints of expectant mothers and medical professionals are gathered by employing qualitative methodologies. The links between the anemia of the mother and the outcomes of labor and delivery are examined using methods that are quantitative. Utilizing a combination of data-driven research and experiential narrative, this mix of methods offers a comprehensive understanding of the subject.